2018
DOI: 10.1080/00949655.2018.1530773
|View full text |Cite
|
Sign up to set email alerts
|

A simulation comparison of imputation methods for quantitative data in the presence of multiple data patterns

Abstract: An extensive investigation via simulation is carried out with the aim of comparing three nonparametric, single imputation methods in the presence of multiple data patterns. The ultimate goal is to provide useful hints for users needing to quickly pick the most effective imputation method among the following: Forward Imputation (ForImp), considered in the two variants of ForImp with the Principal Component Analysis (PCA), which alternates the use of PCA and the Nearest-Neighbour Imputation (NNI) method in a for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Moreover, Solaro et al demonstrated that the relative performance of missForest varied with the MCAR data patterns and did not show a clear advantage. Overall, the imputation accuracy and applicability of missForest is still unclear [ 49 ]. We initially did not include patients with more than 50% missing data as it will require data imputation, which may affect our result.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Solaro et al demonstrated that the relative performance of missForest varied with the MCAR data patterns and did not show a clear advantage. Overall, the imputation accuracy and applicability of missForest is still unclear [ 49 ]. We initially did not include patients with more than 50% missing data as it will require data imputation, which may affect our result.…”
Section: Discussionmentioning
confidence: 99%
“…Yet Shah et al [3] reported that missForest produced substantially biased estimates for variables missing at random (MAR) and poor coverage of confidence intervals compared with CALIBERrfimpute. Solaro et al [8] demonstrated that the relative performance of missForest varied with the MCAR data patterns and did not show a clear advantage. Overall, the imputation accuracy and applicability of missForest is still unclear.…”
mentioning
confidence: 99%
“…Other R packages that implement RF for missing data imputation include the CALIBERrfimpute, randomForest, randomSurvivalForest and randomForestSRC packages [60,61]. Several researchers compare various missing data imputation methods from these packages and conclude that missForest gives lower imputation error [61][62][63].…”
Section: Random Forests Methodsmentioning
confidence: 99%